Heterogeneous returns to U.S. college selectivity and the value of graduate degree attainment - Mai Seki (Bank of Canada, 2013)
Existing studies on the returns to college selectivity have mixed results, mainly due to the difficulty of controlling for selection into more-selective colleges based on unobserved ability. Moreover, researchers have not considered graduate degree attainment in the analysis of labour market returns to college selectivity. In this paper, I estimate the effect of a U.S. four-year undergraduate program's selectivity on wages, including graduate degree attainment. I control for both observed and unobserved selection by extending the model of Carneiro, Hansen and Heckman (2003). There are two channels through which college selectivity affects future labour market outcomes. The first is the wage returns to college selectivity conditional on graduate degree attainment. The second is the effect of college selectivity on the probability of graduate degree attainment and the wage returns to graduate degree attainment. The results show that the former effects dominate the latter, but both are small in magnitude.
Keywords: I21; C30; 330; Labour markets